1992
DOI: 10.2172/1114050
|View full text |Cite
|
Sign up to set email alerts
|

Design and Cost of Solar Photocatalytic Systems for Groundwater Remediation

Abstract: Laboratory and small-scale field experiments have shown that sunlight in conjunction with a simple catalyst can be used to detoxify water contaminated with a variety of hazardous chemicals. This study builds on previous analyses and recent field test data to predict the cost and performance of a representative commercial water detoxification system. Three different solar operating configurations are explored for the treatment of 100,000 gal/day of groundwater contaminated with trichloroethylene. Current costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Similar results were reported by Turchi et al for three different solar operating configurations explored for the treatment of 100000 gal/day of groundwater contaminated with trichloroethylene. They concluded that the current projected costs for solar water detoxification systems were comparable with those for conventional treatment technologies such as carbon adsorption and electric lamp-powered, ultraviolet light/hydrogen peroxide systems.…”
Section: Economic Analysis Of Photocatalytic Systemssupporting
confidence: 88%
“…Similar results were reported by Turchi et al for three different solar operating configurations explored for the treatment of 100000 gal/day of groundwater contaminated with trichloroethylene. They concluded that the current projected costs for solar water detoxification systems were comparable with those for conventional treatment technologies such as carbon adsorption and electric lamp-powered, ultraviolet light/hydrogen peroxide systems.…”
Section: Economic Analysis Of Photocatalytic Systemssupporting
confidence: 88%
“…This leads to opportunities in applications where transportation of chemicals is cumbersome (i.e., geographically isolated regions) or in biological systems that may be sensitive to the addition of chemicals. The performance and costs associated with smallscale groundwater pump and treat systems employing photocatalysis can be comparable to conventional treatment technologies, 90 while negating the need for a continual supply of chemicals. Other emerging opportunities include treatment of waste streams from aquaculture and hydroponics, as both are often practiced in small scale.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The concept of LCOE can also be applied to remediation alternatives to describe the direct costs of electricity consumed and CO 2 emissions produced. A similar metric was described by Turchi et al (1992) where treatment costs per 1,000 gallons treated were compared between systems. Their approach is valid for systems operating on comparable time and volume scale, for example, comparing two or more ex situ technologies operating at high-flow rates, relative to ambient groundwater flow.…”
Section: Levelized Cost Of Energymentioning
confidence: 99%